مناهج الشوكاني الفقهية المستقلة للمذاهب الأربعة في كتابه نيل الأوطار: دراسة تمهيدية = The methodology of al-Shawkani's jurisprudence selections of the four schools of thought from his book Nayl al-Awtar: an introduction - Awang, Abdul Bari; Abdullah, Muhamad Mu'izz (NUNGEMILANG ENTERPRISE, 2021)
يعتبر الإمام الشوكاني عالما مجتهدا إذ إنه متفنن في كثير من العلوم، ولم يترك المؤلف بابا من أبواب العلم الشرعي إلا وتبحر فيه ومن كتبه المشهورة نيل الأوطار في شرح أحاديث الأحكام. لذا، ومن خلال هذا الكتاب قد ظهرت اختياراته الفقهية المخالفة للمذاهب الأربعة، وله اختياراته المستقلة مبنية على القواعد والأسس في استنباط الأحكام، وقد ظن بعض الناس أن المخالفة للمذاهب الأربعة خارقا للإجماع والحق محصورا فيما اتفقت على تلك المذاهب، وفي الحقيقة أن المسائل التي اتفقت عليها المذاهب الأربعة تعبر عن رأي جمهور الفقهاء وغالبا أقرب للصواب، ولكن آراءهم واختياراتهم ليست بحجة لغيرهم وليست إجماعا ملزما إذا تبين أن هناك دليل آخر، لذا فإن هذه الدراسة هي الحاجة إلى حصر اختياراته الفقهية المخالفة للمذاهب الأربعة – وذلك من كتابه نيل الأوطار – التي أبرزها الباحثون السابقون لدلالة أن الحق يدور مع الدليل، علاوة على هذا أن هذه الدراسة القائمة تحاول كشف معالم منهج الشوكاني الذي سلكه في تأليف كتابه لاستنباط الأحكام الفقهية مع بيان آرائه المستقلة. والباحث سيعتمد في دراسته على المنهج التحليلي والوصفي حيث يجمع ويستقرئ الآراء الفقهية للشوكاني من كتاب نيل الأوطار، ثم الدراسات السابقة منها الرسائل والمقالات العلمية والكتب المصنفة حول كتابه وشخصيته ومناهجه الذي تيسر للباحث اطلاع عليها. وحصلت الدراسة أن هناك وجود عدة اختيارات الشوكاني الفقهية المستقلة في كل قسم من كتابه وإن قلّ، وهذا يشير إلى أن أبواب الاجتهاد مفتوح إلى يوم القيامة وللمجتهد أجران؛ أجر إن أصاب، وأجر إن أخطأ. ___________________________________________________ Imam al-Shawkani was a great Islamic scholar who had reached the level of mujtahid and mastered various fields of knowledge. Among his greatest works is the book of Nayl al-Awtar, lectures on Legal Hadith. There are some of his opinions especially in the matter of fiqh that contradict the views of the Imam of the Four Sects (Imam Malik, Imam Hanafi, Imam Syafie, Imam Hanbali). He had his own personal view in determining a hukum based on the method of istinbath hukm. Some people opine that views which contradict the views of the Imam of the Fourth Sects are wrong and out of ijma’. The right views are only based on the views of the Imam of the Four Sects. In actual fact, the views of the Imam of the Four Sects in the matter of fiqh only reflect the views of the majority and its truth can be accepted. Even so, their views are not mandatory arguments that other mujtahids need to follow if there are other arguments. Therefore, this study will gather his personal views that contradict the views of the Imam of the Four Sects in his book Nayl al-Awar through the highlights of previous literature review and explain that the truths are based on arguments. The methodology used in this study is qualitative in nature by analyzing the data obtained descriptively. The primary source referred to is the original work composed by Imam al-Shawkani. While the secondary source is previous studies such as theses, journal articles and books. The result of the study shows that there are several personal views of Imam al-Shawkani that contradict the Imam of the Four Sects views in his book, Nayl al-Awtar. This has proven that the door of ijtihad for a mujtahid is open until the Day of Judgment. If the ijtihad is correct then two rewards are bestowed, if not, one reward is bestowed.